Extravagant in the Koran (Journal of the College of Education for Women, 2019)
This research deals with a disease of the diseases our Muslim society, which works in thebody operate deadly epidemics in the bodies and of bodies, but it is extravagant; has spreadand rampant in our uncle everything which threatens significant damage in this life and theafterlife, as well as that it shows that Alasirafla limited to extravagant in wasting money andwith this blessing should not have, and not be used as created him .Excessive linked to all aspects of life, physical and moral it has many pictures and variousforms, came at the forefront of research and five sections:The first topic: the meaning of truth and extravagant.The second topic: Photos extravagant reprehensible contained in the Koran.The third topic: defamation extravagant and wasteful in the Koran .Section IV: penalty extravagant and wasteful in this world and the afterlife.Section V: extravagant effects on the individual and society.The conclusion stating the most important findings through research.